2014
DOI: 10.1021/tx500011m
|View full text |Cite
|
Sign up to set email alerts
|

DNA Cleavage and Detection of DNA Radicals Formed from Hydralazine and Copper (II) by ESR and Immuno-Spin Trapping

Abstract: Metal ion-catalyzed oxidation of hydrazine and its derivatives leads to the formation of the hydrazyl radical and subsequently to oxy-radicals in the presence of molecular oxygen. Here we have examined the role of Cu2+-catalyzed oxidation of hydralazine in the induction of DNA damage. Neither 5, 5-dimethyl-1-pyrroline-N-oxide (DMPO) nor dimethyl sulfoxide (DMSO) were effective in inhibiting hydralazine-Cu2+-induced DNA damage. Singlet oxygen did not appear to participate in this DNA cleavage. The one-electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…After introducing Cu(OTf) 2 into the reaction system (Notably, other metal salts were also tested, see Figs S1 and S2 in supplementary information for details), the desired nitrogen-centered radical was successfully detected ( Fig. 5B ) 52 53 , where the g factor was 2.0059. The above results might demonstrate the existence of nitrogen-centered radical and stabilization effect of Cu(OTf) 2 to nitrogen-centered radical.…”
Section: Resultsmentioning
confidence: 99%
“…After introducing Cu(OTf) 2 into the reaction system (Notably, other metal salts were also tested, see Figs S1 and S2 in supplementary information for details), the desired nitrogen-centered radical was successfully detected ( Fig. 5B ) 52 53 , where the g factor was 2.0059. The above results might demonstrate the existence of nitrogen-centered radical and stabilization effect of Cu(OTf) 2 to nitrogen-centered radical.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, previous studies have shown that hydralazine exposure induced both DNA cleavage and damage [24, 25]. The lack of efficient DNA repair is often an advantage for cancer therapy (especially radio- and chemotherapy), based on the concept of synthetic lethality, which states that cancer cells are more proliferative and thus more susceptible to induced DNA damage than normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…4a ) was a triplet-of-sextets (blue line in Fig. 4b ) with HFCs of a N = 13.58 G, a H = 16.64 G, a γ−N = 2.50 G; this signal was assigned to a DMPO-trapped N-centered radical adduct (DMPO-N·) 31 32 . The small γ-N hyperfine coupling constant clearly indicated the existence of the Co-diazo radical.…”
Section: Resultsmentioning
confidence: 99%